User Acceptance of Mobile Banking in Developing Country: A Path Analysis of Conceptual Model - Safitri, Eristya Maya; Arista Pratama; Amalia, Indira S.; Alifansa, Dimas Mirza; Riyantoko, Prismahardi Aji (Journal of Advances in Information and Industrial Technology, 2024)
Mobile banking is one of the information systems that has been proliferating. Its use in Indonesia has increased yearly, with transactions exceeding 4 trillion in 2021. Bank Negara Indonesia, or BNI, is one of the banks that adopted mobile banking service. The increased use also reflects the challenges in continuity to receiving mobile banking services, such as security and privacy, risk, trust, and mobile usability. This research aims to find out how security and privacy, risk, trust, and mobile usability affect mobile banking acceptance by using the Technology Acceptance Model (TAM). This research was conducted by survey and using simple random sampling to determine the respondents. Descriptive and analytical data are evaluated using the SEM technique. The proposed hypothesis is supported if the p-value is less than or equal to 0.005. The result shows that the acceptance of mobile banking is affected significantly by security and privacy, perceived trust, and mobile usability, with p-values for each construct being 0.027, 0.000, and 0.015. At the same time, perceived risk has an insignificant effect on mobile banking acceptance, with p- a value of 0.094. The other finding is that perceived risk and perceived trust have significantly affected mobile banking acceptance with a p-value of 0.000. Security and privacy, risk, trust, and mobile usability are critical factors for mobile banking to be accepted by its users.